(untitled) (Research, Society and Development, 2021)
This article aims to promote the education of argumentative education in contemporary schools for conflict management, based on active methodologies. The work defends proposals of an argumentative nature, based on the New Rhetoric, directed to the diverse teaching modalities for students, as well as for initial and continuous training of teachers and other school employees. Thus, to arrive at the results, it values a descriptive and qualitative research work. The results lead to consider that, if an argument to be worked on in a continuous and effective way can mitigate or avoid in educational environments. In this way, it was concluded that continuing argumentative education with active methodologies, can motivate respect for the act of speech, enable listening and dialogue, value different points of view, facilitate persuasion and persuasion, improve the businessmen who speak and interlocutors in and outside schools.